Are Religious People Any Happier?: Probing the Divine Relationship, Organizational Religiosity and the Role of Education and Income in the United States - Upenieks, Laura (Journal of religion and health, 2025)
Findings from a large body of research tend to suggest that greater involvement in religion is associated with greater happiness. The current study seeks to extend this literature by examining both organizational and non-organizational religiosity, especially the importance of the divine relationship, in predicting happiness. In addition, this study tests whether the relationship between religiosity and happiness is conditional on two elements of socioeconomic status: education and income, which themselves have complicated relationships with happiness. Analyses draw from nationally representative data from the 2017 Values and Beliefs of the American Public Survey (Baylor Religion Survey, N = 1,262), collected in the United States. Results suggest that greater religious attendance, stronger perceptions of divine control, and a more secure attachment to God were associated with greater happiness. The benefits of religiosity for happiness were also stronger for those with a lower education and income. The implications of the results are discussed. Taken together, the findings of this study show that the benefits of religious involvement for subjective well-being are not distributed evenly across the socioeconomic ladder.